Analytical Method Establishment for Determination of the Mixture of Dexchlorpheniramine Maleate and Dexamethasone Tablet using High Performance Liquid Chromatography - S Si, Ulita
Background and purpose:The prevalence of allergic diseases is rising dramatically in both developed and developing countries. High prevalence of allergic diseases increased the need of anti-allergy drugs. The combination of dexchlorpheniramine maleate and dexamethasone are one of the drugs prescribed to suppress allergy symptoms. Indonesian specialite drugs 2010 described 15 tablets containing a mixture of the two substances. Dexchlorpheniramine maleate was an antihistamine that relieved the symptoms of allergic and dexamethasone was anti-inflammatory drug synergistically as an anti- allergic. The National Agency of Drug and Food Control (NA-DFC) performed pre-market evaluation and post-market for public protection. NA-DFC required validated analytical methods for evaluating the quality of products and quantitating dexchlorpheniramine maleate and dexamethasone. The validated methode was AOAC method using HPLC, was expected to be used for routine analysis in NA- DFC. Method: The analysis was performed on a reversed-phase C18 column, mobile phase consisted of 7.5 mM monobasic potassium phosphate in methanolwater (60:40) at a constant flow rate 1 mL/menit, temperature column 32 0 C, injection volume 20 µL with uv detection at 254 nm. In this experiment, standard stock solution was diluted by methanol-water (50:50) and 10 mL methanol-water (50:50) was added to sample before being diluted by mobile phase. Results: The method was validated in term of linearity, precision, accuracy and spesificity. The response was linear in range of 16 –112 ppm and 4 - 28 ppm for dexchlorpheniramine maleate (r = 0.9999) and dexamethasone (r = 0.9999) respectively. Limit of detection 0.23 mg/g respectively for dexchlorpheniramine maleate and 0.05 mg/g for dexamethasone, limit of quantitation was 0.69 mg/g for dexchlorpheniramine maleate dan 0.15 mg/g for dexamethasone. The relative standar deviation values for interday (1.33%; 1.75%; 1.56%), intraday 1.16% respectively for dexchlorpheniramine maleate and (1.42%; 0.72%; 1.85%) interday and 0.47% intraday, respectively for dexamethasone. Recoveries range of sample spiked placebo were from 96.7 to 99.66 % with RSD 1.07% for dexchlorpheniramine maleate and 92.19 to 96.3 % with RSD 0.83% for dexamethasone. The established method used has good accuracy and precision. The established method was applied to determination of dexchlorpheniramine maleate and dexamethasone tablet in market. The concentration of dexchlorpheniramine maleate and dexamethasone used validated method were 97.10–102.25 % for dexchlorpheniramine maleate and 91.55–101.69 % for dexamethasone of the amount list on the label.